2014
DOI: 10.3324/haematol.2014.106088
|View full text |Cite
|
Sign up to set email alerts
|

The truncated RUNX1/ETO activates VLA-4-dependent adhesion and migration of hematopoietic progenitor cells

Abstract: In the acute myeloid leukemia (AML)-associated chromosomal translocation t(8;21), the hematopoietic master regulator RUNX1 (also known as AML1, CBFα2 or PEBP2αB) located on chromosome 21 is fused to almost the entire ETO gene (also known as MTG8 or RUNX1T1) on chromosome 8, thereby generating the fusion protein RUNX1/ETO. RUNX1/ETO is a strong repressor of myeloid differentiation functioning via the dysregulation of genes connected to hematopoietic stem cell (HSC) maturation.1 In this study, we analyzed whethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 12 publications
1
15
0
Order By: Relevance
“…PSLG-1 repression results in an impediment of cellular adhesion, which was restored after depletion of AML1/ETO. Furthermore, the AML1/ETO9a splice variant was shown to influence adhesion and migration of hemopoietic progenitor cells via the regulation of VLA-4 expression 12 . This confirms that the deregulation of adhesion molecules and of migratory properties is an important feature of t(8; 21) + AML.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PSLG-1 repression results in an impediment of cellular adhesion, which was restored after depletion of AML1/ETO. Furthermore, the AML1/ETO9a splice variant was shown to influence adhesion and migration of hemopoietic progenitor cells via the regulation of VLA-4 expression 12 . This confirms that the deregulation of adhesion molecules and of migratory properties is an important feature of t(8; 21) + AML.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, genes encoding for proteins involved in cellular adhesion and/or migration were found to be common targets for the AML1, AML2 and AML3 transcription factors 9 , and aberrant expression of adhesion molecules has been described in acute lymphoblastic leukemia cases carrying the TEL/AML1 (or ETV6/RUNX1) fusion gene 10 . Moreover, expression of CD44 11 , VLA-4 12 and LFA-1(or CD11a) 13 adhesion molecules has been found to be directly regulated by AML1/ETO.…”
mentioning
confidence: 98%
“…19 Peptide-mediated interruption of RE tetramerization was performed using the NHR2-inhibitor peptide described before. 37 Efficacy of the shRNA against the RE breakpoint sequences was recently demonstrated.…”
Section: Methodsmentioning
confidence: 99%
“…A number of these studies have identified an important role for RUNX1 in regulating cell adhesion and migration programs (Lie et al, ; Michaud et al, ; Wotton et al, ). Furthermore, RUNX1 regulation of several genes encoding cell adhesion molecules has been reported, including VLA‐4 (also known as α4β1; Ponnusamy et al, ), CD44 (Peterson et al, ), ITGAL (Puig‐Kroger et al, ), and PSGL1 (Ponnusamy et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, RUNX1 regulation of several genes encoding cell adhesion molecules has been reported, including VLA-4 (also known as α4β1; Ponnusamy et al, 2014), CD44 (Peterson et al, 2007), ITGAL (Puig-Kroger et al, 2003), and PSGL1 (Ponnusamy et al, 2015).…”
mentioning
confidence: 99%